Implementation of lean six sigma to improve the quality of service of a company in the restaurant sector - Paz Acosta, Andrea Gianella (2025)
The research proposed to implement Lean Six Sigma in a restaurant company to improve the service quality of Siu Mai snacks delivered via delivery. The study was based on a pre-experimental design with a quantitative approach and evaluating customer perception before and after using the Servqual method. In the initial analysis, lack of employee induction, poor order management and lack of process evaluation were found as causes of low quality. Using DMAIC, processes were improved with BPMN and Kanban to follow the order flow, which optimized processes, reduced waiting times and improved service quality. The results showed that the Servqual score improved from 4.07 to 6.09, while the CP and CPK indicators improved significantly. It was concluded that the implementation of Lean Six Sigma using tools such as VSM, Kanban and SIPOC helped improve service quality and customer satisfaction by optimizing processes, reducing waiting times and improving the ability to respond empathetically to customers.